MULTIPLE INTELLEGENCES AND ITS FUTURE POSSIBLE IMPLICATION IN ENGLISH LANGUAGE TEACHING - Nor, Hidayah (English Education: Jurnal Tadris Bahasa Inggris, 2015)
Multiple Intelligence was proposed by Howard Gardner in 1983 as a model of intelligences that classify intelligences into various specific (primarily sensory) modalities, rather than seeing it as dominated by a single general ability. He has questioned the idea that intelligence is a single entity, that it results from a single factor, and that it can be measured simply via IQ tests.In this study, the writer tried to explain the history of multiple intelligence, the definition and types of multiple intelligences, and also the future possible implication of Multiple Intelligence in the teaching of English as a Foreign Language in Indonesia.